Biomarkers of pro- and antioxidant systems in guinea pigs’ blood in late periods of experimental allergic alveolitis development and their correction with thiotriazolin - Fyrduchco – Regeda, Mariana Mukchailivna; Solvar, Zoryana Ljubomurivna; Baida, Mariana Ljubomurivna (Journal of Education, Health and Sport, 2017)
Hypersensitivity pneumonitis is a potentially fatal immunological lung disease caused by occupational or environmental exposure to specific antigens and resulting from lymphocytic and frequently granulomatous inflammation of the peripheral airways, alveoli, and surrounding interstitial tissue which develops as the result of a non-IgE-mediated allergic reaction to a variety of organic materials or low molecular weight agents that are present in the workplace. The offending agents can be classified into six broad categories that include bacteria, fungi, animal proteins, plant proteins.The cornerstone of treatment is early removal from exposure to the eliciting antigen, although the disease may show an adverse outcome even after avoidance of exposure to the causal agent. The primary insults cause the greatest production of reative oxygen species, which contributes to oxidative damage by attacking all macromolecules, including lipids, proteins and nucleic acids, leading to defects in their physiological function.